الأمن الطاقوي الجزائري - تأصيل نظري ايتيمولوجي- - بن حمزة نبيل (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
يعد مفهوم الامن الطاقوي من المفاهيم المستحدثة في الدراسات الأمنية، وهو يعبر عن التطور الذي حصل في الحقل من خلال تفكيك مفهوم الامن؛ بحيث تهدف هذه الدراسة إلى تأصيل مفاهيمي ونظري للأمن الطاقوي الجزائري كمحتوى في الدراسات الأمنية وكذا توضيح المحددات الأساسية للمفهوم، وهو مفهوم لا يقل أهمية عن باقي المفاهيم في الدراسات الأمنية؛ لأنه مفهوم متداخل مع بقية المفاهيم ويكملها، كما يعتبر محرك جوهري لبناء أمن اقتصادي و أمن قومي للجزائر، لذلك فعلى الدول المنتجة للموارد الطاقوية وفي سبيل أمنها الطاقوي أن تبني مقاربة للأمن الطاقوي تركز على خصوصيتها ، حيث سنحاول من خلال هذه الورقة البحث في مفهوم الأمن الطاقوي، والبحث في المقاربات التي تساهم في بناء أمن طاقوي يعزز بناء و قوة الأمن القومي الجزائري، Abstract: The concept of energy security is considered as one of the most important concepts that are developed within the field of security studies. It represents and expresses the development and changes that happened in the field. On this basis, the present study aims to establish both conceptual and theoretical aspects of Algerian energy security as a subject matter in the field of security studies. This study also aims to clarify the basic determinants of the concept, which are equally important as the main one in, for the reason that it intertwines and complements the rest of the concepts, and it is considered an essential engine for building the Algerian economic and national security. Therefore, countries that produce energy resources and wish to secure their energy must adopt an approach that focuses on its specificity. Furthermore, we will attempt through this study to analyse the concept of energy security and investigate some approaches that contribute to building energy security which enhances the building and strength of the Algerian national security,